Chemical fractionations and mobility of heavy metals in soils of eastern Uttar Pradesh - PATRA, ABHIK; SINGH, SATISH KUMAR; CHATTOPADHYAY, ARGHYA; SHARMA, VINOD KUMAR; REKWAR, RAVINDRA KUMAR (The Indian Journal of Agricultural Sciences, 2021)
In the current investigation, an attempt has been made to assess the various chemical forms and mobility factor (MF) for lead (Pb), cadmium (Cd), chromium (Cr) and nickel (Ni) in four soils of eastern Uttar Pradesh. For this purpose, two different surface soil samples were collected from each of Entisol, Inceptisol, Vertisol and Alfisol soil orders during 2019–20. The modified Tessier sequential extraction procedure was applied to determine the chemical pools of Pb, Cd, Cr and Ni in each soil. Results indicated that total metal content follows the order of Pb>Cr>Ni>Cd across the orders, whereas mobility factor of micronutrients could be arranged as: Cd>Pb>Ni>Cr. The bioavailable metal fraction of all micronutrients, i.e. exchangeable pool (F1) was maximum in Inceptisol. The highest carbonate bound (F2), Fe–Mn oxides bound (F3), organically bound (F4) and residual (F5) fraction were recorded in Vertisol, Alfisol, Inceptisol and Alfisol, respectively for all heavy metals. The mean percentage value of Pb and Ni fractions were in the order of F5>F3>F4>F2>F1, whereas Cd whose chemical fractions follows the order of F2>F3>F4>F5>F1. The Pb was highly mobile in Vertisol, Ni in Inceptisol, while Cd and Cr in Entisol. Therefore, availability and mobility of heavy metals in the soil environment depends mainly on their association with various chemical fractions of the soil which relies on the mineralogical origin of the metals.